Extraction of Nanocellulose from Bagasse Using Acid Hydrolysis Method - Zaharani, Rethanita; Manurung, Posman; Firdaus, Iqbal; Asmi, Dwi; Abdurrahman, Ahmad Faruq (Journal of Energy, Material, and Instrumentation Technology, 2024)
The acid hydrolysis method was used to extract nanocellulose from bagasse. This study aims to prepare nanocellulose from sugarcane bagasse by acid hydrolysis method and to know the results of characterization with X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and Fourier Transform Infrared (FTIR). In this study, 4 samples were made with variations of H2SO4 of 19, 29, 39 and 45%. XRD analysis shows that with the increase of sulfuric acid, the percentage of each sample increases, but in the 39% sample, there is a decrease in purity because there are still areas of cellulose that have yet to disappear. The phase identification results show that in the sample with 19, 29, and 39% addition, H2SO4 Iα, Iβ, and thenardite phases were formed. In the sample, 45% only form Iα and Iβ phases with a resulting particle size of 2.83 nm and a degree of crystallinity of 55.52%. The results of the SEM test analysis show that the image pattern has stone structures that overlap each other. The results of FTIR analysis show that the functional groups detected are O – H, C – H, C ≡ C, C = C, H – C – H, C – O, and C – O – C, which indicates the presence of nanocellulose.